Chest wall restriction device for modeling respiratory challenges and dysfunction - Ribeiro Rodrigues, Victoria; Mejia, Lizuannette; Zucchi, Rafael G.; Davenport, Paul W.; Napoli, Nicholas J. (Frontiers in Medical Engineering, 2025)
Breathing relies on unrestricted movement of the chest wall to maintain O2 and CO2 balance. Understanding the effects of chest and abdominal restrictions on respiratory function is critical for studying conditions such as respiratory diseases, extreme environments, and load-induced impairments. However, existing methods to simulate these restrictions are limited, lacking the ability to provide both static and dynamic conditions or precise load control. To address these gaps, we developed a novel chest wall and abdomen restriction device capable of independently applying and measuring static and dynamic loads with adjustable and reproducible force levels. Separate bands for the chest and abdomen enable targeted restrictions. In static conditions, the bands are immobilized, preventing any movement of the chest and abdomen. In dynamic conditions, constant force springs provide resistance, allowing movement when sufficient force is applied. Integrated sensors quantify applied loads and respiratory mechanics. To validate the device, healthy participants underwent pulmonary function testing under baseline, static, and dynamic restriction conditions. Significant reductions in forced expiratory volume (FEV1) and forced vital capacity (FVC) were observed under restrictions compared to baseline. Other respiratory metrics also differed significantly, highlighting distinct effects of static and dynamic restrictions. Pressure variability tests confirmed reproducibility and adjustability of loads, while displacement data from linear variable differential transducers (LVDTs) validated the device’s ability to distinguish static and dynamic effects. This device addresses prior limitations by enabling precise, reproducible loading and independent control of chest and abdominal restrictions, supporting research into respiratory diseases, extreme environments, and respiratory mechanics. Our results demonstrate its potential to advance respiratory function research and expand clinical and experimental applications.